The Potential and Challenges of AI Adoption in Marketing Across Africa: Opportunities for Digital Transformation - Alice, Sadiku Ifeoluwa; Ebuka, Olaoluwa Diallo (Business and Investment Review, 2024)
Artificial Intelligence (AI) has the potential to revolutionize marketing practices across Africa, offering businesses tools to enhance customer engagement, personalize experiences, and optimize decision-making. This study explores the opportunities, challenges, and feasibility of adopting AI in marketing within the African context. Through a mixed-methods approach combining literature review, surveys, interviews, case studies, and data analysis, the research identifies key drivers of AI adoption and the barriers hindering its widespread implementation. The findings reveal that while countries like South Africa, Kenya, and Nigeria are at the forefront of AI adoption, challenges such as limited digital infrastructure, high costs, skill shortages, and consumer skepticism remain significant obstacles. Furthermore, the lack of comprehensive policies and region-specific AI solutions further impedes the technology's full potential. Despite these challenges, the study highlights the immense opportunities AI presents in sectors like e-commerce and fintech, where localized AI solutions can drive inclusive economic growth. The research provides strategic recommendations for overcoming barriers, including investments in digital infrastructure, capacity-building initiatives, and the development of affordable, contextually relevant AI solutions. Ultimately, the study argues that with the right investments and policy support, AI has the potential to play a pivotal role in transforming marketing practices and contributing to Africa's digital and economic growth.